2022
DOI: 10.1002/cncr.34403
|View full text |Cite
|
Sign up to set email alerts
|

OER‐073: A multicenter phase 2 study evaluating the role of pazopanib in angiosarcoma

Abstract: BACKGROUND: Angiosarcomas are rare mesenchymal sarcomas that can present as primary cutaneous or noncutaneous disease. They express a variety of vascular endothelial growth factor receptors. The authors hypothesized that the treatment of angiosarcoma with pazopanib, a multikinase inhibitor with activity against vascular endothelial growth factor receptors, would result in disease response and prolonged disease stabilization. METHODS: This was an open-label, phase 2 trial of pazopanib in patients who had incura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In another clinical trial, the median PFS was 4.3 months with pazopanib for chemotherapy‐resistant angiosarcoma 19 . The median PFS was 132 days (4.4 months) in the present study, suggesting that the efficacy of pazopanib is comparable to that seen in previous clinical studies, even in a Japanese cohort 18,19 . The most common G3 or more AEs was hypertension, followed by liver dysfunction, which suggests that pazopanib is tolerable for the treatment of advanced angiosarcoma 18,19 .…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In another clinical trial, the median PFS was 4.3 months with pazopanib for chemotherapy‐resistant angiosarcoma 19 . The median PFS was 132 days (4.4 months) in the present study, suggesting that the efficacy of pazopanib is comparable to that seen in previous clinical studies, even in a Japanese cohort 18,19 . The most common G3 or more AEs was hypertension, followed by liver dysfunction, which suggests that pazopanib is tolerable for the treatment of advanced angiosarcoma 18,19 .…”
Section: Discussionsupporting
confidence: 78%
“…A recent multicenter, phase 2 study evaluating pazopanib for uncurable angiosarcoma reported median PFS of 14.4 weeks and 3-month PFS of 54.6% (95% CI 36.0-82.9%). 18 In another clinical trial, the median PFS was 4.3 months with pazopanib for chemotherapy-resistant angiosarcoma. 19 The median PFS was 132 days (4.4 months) in the present study, suggesting that the efficacy of pazopanib is comparable to that seen in previous clinical studies, even in a Japanese cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations